2017
DOI: 10.1002/adhm.201601269
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Polymeric Membrane with Enhanced Mechanical and Biological Properties to Control the Degradation of Magnesium Alloy

Abstract: To achieve enhanced biological response and controlled degradation of magnesium alloy, a modified biodegradable polymer coating called polycaprolactone (PCL) is fabricated by a thermal approach in which the heat treatment neither alters the chemical composition of the PCL membrane nor the rate of magnesium ion release, pH value, or weight loss, compared with the untreated sample. The changes in the crystallinity, hydrophilicity, and oxygen content of heat-treated PCL coating not only improve the mechanical adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 63 publications
0
19
0
1
Order By: Relevance
“…Hence, it seems to be the new strategy for designing next-generation orthopedic substitutes by developing biomaterials with an osteoimmunomodulatory function to promote osteogenesis and, subsequently, generate a suitable osteoimmune microenvironment. Recently, stimulation of bone formation by magnesium ions released from biomaterials (e.g., metallic implant, bio-polymer, and bio-ceramic) has drawn much attention owing to the high efficacy, low cost, and reduced complication [ [32] , [33] , [34] , [35] ]. The delivery of magnesium ions at a suitable range of concentrations contributes to osteogenesis by promoting osteoblastic activity and inhibiting osteoclastic activity and facilitating the bone mineralization process [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it seems to be the new strategy for designing next-generation orthopedic substitutes by developing biomaterials with an osteoimmunomodulatory function to promote osteogenesis and, subsequently, generate a suitable osteoimmune microenvironment. Recently, stimulation of bone formation by magnesium ions released from biomaterials (e.g., metallic implant, bio-polymer, and bio-ceramic) has drawn much attention owing to the high efficacy, low cost, and reduced complication [ [32] , [33] , [34] , [35] ]. The delivery of magnesium ions at a suitable range of concentrations contributes to osteogenesis by promoting osteoblastic activity and inhibiting osteoclastic activity and facilitating the bone mineralization process [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that Mg-incorporated biomaterial surfaces could increase cellular attachment [ 64 , 65 ]. Our previous studies have also found an optimal range of Mg 2+ levels, which could upregulate cell viability and proliferation of human osteoblasts (SaOS-2) and mouse pre-osteoblasts (MC3T3-E1) [ [66] , [67] , [68] ]. Accordingly, the T-Moderate should be the most appropriate composite with the above data.…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium, its alloys [10][11][12][13] and derivatives [14][15][16] have been extensively studied as replacements for non-degradable metallic implants e.g., titanium alloys in bone surgeries. Mg 2+ modified biomaterials have shown superior osteogenic capacity in many reports [14][15][16][17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%